E-cadherin acts as a positive regulator of the JAK-STAT signaling pathway during Drosophila oogenesis - Mallart, Charlotte; Chalvet, Fabienne; Netter, Sophie; Torres, Alba Yurani; Poidevin, Mickael; Montagne, Jacques; Pret, Anne-Marie; Malartre, Marianne (Frontiers in Cell and Developmental Biology, 2022)
The JAK-STAT pathway is evolutionary conserved. The simplicity of this signaling in Drosophila, due to the limited redundancy between pathway components, makes it an ideal model for investigation. In the Drosophila follicular epithelium, highly stereotyped functions of JAK-STAT signaling have been well characterized, but how signaling activity is regulated precisely to allow the different outcomes is not well understood. In this tissue, the ligand is secreted by the polar cells positioned at each follicle extremity, thus generating a gradient of JAK-STAT activity in adjacent cells. One way to control the delivered quantity of ligand is by regulating the number of polar cells, which is reduced by apoptosis to exactly two at each pole by mid-oogenesis. Hence, JAK-STAT activity is described as symmetrical between follicle anterior and posterior regions. Here, we show that JAK-STAT signaling activity is actually highly dynamic, resulting in asymmetry between poles by mid-oogenesis. Interestingly, we found similar temporal dynamics at follicle poles in the accumulation of the adherens junction E-cadherin protein. Remarkably, E-cadherin and JAK-STAT signaling not only display patterning overlaps but also share functions during oogenesis. In particular, we show that E-cadherin, like JAK-STAT signaling, regulates polar cell apoptosis non-cell-autonomously from follicle cells. Finally, our work reveals that E-cadherin is required for optimal JAK-STAT activity throughout oogenesis and that E-cadherin and Stat92E, the transcription factor of the pathway, form part of a physical complex in follicle cells. Taken together, our study establishes E-cadherin as a new positive regulator of JAK-STAT signaling during oogenesis.